Valence band dispersion measured in the surface normal direction of CH3NH3PbI3 single crystals. (24th December 2019) - Yang, Jin-Peng; Ren, Si-Xian; Yamaguchi, Takuma; Meissner, Matthias; Cheng, Li-wen; Zhou, Lei; Ideta, Shinichiro; Tanaka, Kiyohisa; Kera, Satoshi
Abstract: The electronic structure of methylammonium lead iodide (CH3 NH3 PbI3 ) single crystal surface has been studied by angle-resolved photoemission spectroscopy with synchrotron radiation. From energy dependence of normal emission spectra, we observe a top valence band dispersion of about 0.2 eV, which is originated from hybridized states of Pb-6s and I-5p. The inner potential of CH3 NH3 PbI3 is estimated to be −3 eV. Moreover, obtained lattice constants along the surface normal direction is 6.25 Å, which agree well to the lattice constant of a cubic phase in CH3 NH3 PbI3, confirm the structure of surface layers at 300 K is predominated by a cubic phase.